Histamine 3 receptor inverse agonist Samelisant (SUVN-G3031): Pharmacological characterization of an investigational agent for the treatment of cognitive disorders. (June 2021) - Nirogi, Ramakrishna; Grandhi, Venkata R; Medapati, Rajesh B; Ganuga, Narender; Benade, Vijay; Gandipudi, Sudhakar; Manoharan, Arunkumar; Abraham, Renny; Jayarajan, Pradeep; Bhyrapuneni, Gopinadh; Shinde, Anil; Badange, Rajesh K; et al.
Background: Central histamine H3 receptors are a family of presynaptic auto and heteroreceptors. Blockade of the presynaptic H3 receptors activates the downstream pathway(s) involved in the processes of learning and memory, making it a potential therapeutic option for ameliorating cognitive dysfunction. Samelisant (SUVN-G3031) is a potent and selective inverse agonist at the H3 receptors. Aim: The aim of this research is to study the effects of Samelisant in diverse animal models of cognitive functions. Methods: The effects of Samelisant on cognitive functions were studied using social recognition, object recognition and Morris water maze tasks. Neurochemical and electrophysiological effects of Samelisant were monitored using microdialysis and electroencephalography techniques. Results: Samelisant showed procognitive effects in diverse animal models of cognition at doses ranging from 0.3 to 3 mg/kg, per os ( p.o .) (social recognition and object recognition task). Samelisant significantly increased the brain acetylcholine levels in the cortex at doses of 10 and 20 mg/kg, p.o . In the Morris water maze task, combined administration of suboptimal doses of Samelisant and donepezil resulted in procognitive effects significantly larger than the either treatment. Similarly, Samelisant significantly potentiated the effects of donepezil on pharmacodynamic biomarkers of cognition i.e. acetylcholine levels in brain and neuronal theta oscillations. Conclusion: Samelisant may have potential utility in the treatment of cognitive deficits associated with hypocholinergic state.